Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/en12193801
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Preventive Maintenance of Wind Turbine Components with Imperfect Continuous Condition Monitoring

Abstract: Among the different maintenance techniques applied to wind turbine (WT) components, online condition monitoring is probably the most promising technique. The maintenance models based on online condition monitoring have been examined in many studies. However, no study has considered preventive maintenance models with incorporated probabilities of correct and incorrect decisions made during continuous condition monitoring. This article presents a mathematical model of preventive maintenance, with imperfect conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In 2019, ref. [102] proposed a mathematical framework for the preventive maintenance of wind turbine components with imperfect continuous condition monitoring in the interval (0, τ). The decision to perform maintenance on the wind turbine component relies on data obtained from the sensors.…”
Section: Models With Non-constant Probabilities Of Correct and Incorr...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, ref. [102] proposed a mathematical framework for the preventive maintenance of wind turbine components with imperfect continuous condition monitoring in the interval (0, τ). The decision to perform maintenance on the wind turbine component relies on data obtained from the sensors.…”
Section: Models With Non-constant Probabilities Of Correct and Incorr...mentioning
confidence: 99%
“…The expected maintenance cost per unit time is calculated by dividing the average maintenance cost for the regeneration cycle by its average duration [102].…”
Section: Models With Non-constant Probabilities Of Correct and Incorr...mentioning
confidence: 99%
“…Second, operational management of remote monitoring and diagnostics has attracted research attention in recent years (Guillén et al 2016;Raza and Ulansky 2019;Raja et al 2017). Kurz (2016) and Kurz and Pibernik (2016) analyzed the effects of advanced information created and collected by real time condition monitoring for maintenance services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the company also faces imperfect prediction signals such as false positives and false negatives (Topan et al 2018). Another example of this problem is the maintenance services for wind turbines installed worldwide (Raza and Ulansky 2019). This imperfect monitoring considerably influences maintenance services (Topan et al 2018;Nguyen et al 2019); however, few studies have investigated the problem.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the optimum scheduled maintenance interval should be 113 days instead of a typical industry schedule of 180 days, whereas Kerres et al (2014) [11] found that corrective maintenance done upon a failure, is a better option for a V44-600 kW turbine. Raza and Ulansky (2019) [12] applied imperfect continuous condition monitoring which considers correct and incorrect decisions about preventive maintenance for wind turbines. They concluded that a preventive maintenance could reduce the average lifetime maintenance cost 11.8 times comparing the corrective maintenance for wind turbine blades.Overall, several of the previous studies diverse in their findings and new approaches to data analysis and modeling may be needed to provide more cohesive guidance to wind turbine O&M managers.…”
mentioning
confidence: 99%